2011
DOI: 10.1111/j.1365-2184.2011.00787.x
|View full text |Cite
|
Sign up to set email alerts
|

Loss of macrophage migration inhibitory factor impairs the growth properties of human HeLa cervical cancer cells

Abstract: MIF plays a pivotal role in proliferation and tumourigenesis of human HeLa cervical carcinoma cells, and may represent a promising therapeutic target for cancer intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Further studies revealed that MIF transcription is induced by hypoxia-inducible factor 1 α (HIF1 α ) and is physically linked to HIF1 α through COP9 signalosome subunit 5 (CSN5) interaction [ 42 , 44 , 45 ]. MIF can potentially inhibit apoptosis and p53-mediated growth arrest and its depletion impairs cell proliferation in cancer [ 6 , 7 , 46 – 48 ]. It was suggested that MIF's action of blocking apoptosis is dependent on its catalytic oxidoreductase activity.…”
Section: Mif Structure and Functionmentioning
confidence: 99%
“…Further studies revealed that MIF transcription is induced by hypoxia-inducible factor 1 α (HIF1 α ) and is physically linked to HIF1 α through COP9 signalosome subunit 5 (CSN5) interaction [ 42 , 44 , 45 ]. MIF can potentially inhibit apoptosis and p53-mediated growth arrest and its depletion impairs cell proliferation in cancer [ 6 , 7 , 46 – 48 ]. It was suggested that MIF's action of blocking apoptosis is dependent on its catalytic oxidoreductase activity.…”
Section: Mif Structure and Functionmentioning
confidence: 99%
“…5 The knockdown of MIF also induced cell cycle arrest of G1/S transition and increased cell adhesion and therefore impaired their migratory capacity. 6 D-dopachrome tautomerase (D-DT) is the only known MIF homologue determined from human genome. It shares 38% amino acid identity with MIF, and its tertiary structures are remarkably similar.…”
mentioning
confidence: 99%
“…Although T cells are known as the main source of MIF production, other cell types including macrophages are also involved in MIF production and secretion. MIF is also considered as a proinflammatory cytokine with a range of targets which modulate the expression of a number of inflammatory molecules, including TNF-α, IL-6, IL-1b, IL-2, IL-8, and IFN-γ [Wang et al, 2012;Zhang et al, 2013] and playing an important immune regulatory role in several inflammatory diseases such as rheumatoid arthritis and atherosclerosis [Xiao et al, 2011;Saeedi et al, 2013].…”
Section: Introductionmentioning
confidence: 99%